The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/1687814019838353
|View full text |Cite
|
Sign up to set email alerts
|

Resonance risk and global sensitivity analysis of a straight–curved combination pipe based on active learning Kriging model

Abstract: The resonance failure of straight-curved combination pipes conveying fluid which are widely used in engineering is becoming a serious issue. But there are only few studies available on the resonance failure of combination pipes. The resonance failure probability and global sensitivity analysis of straight-curved combination pipes conveying fluid are studied by the active learning Kriging method proposed in this article. Based on the Euler-Bernoulli beam theory, the dynamic stiffness matrices of straight and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Thus, it is worth to explore the dynamics of the straight-curved combination fluid-conveying pipe. Indeed, a few researchers have studied this kind of pipe [34][35][36][37][38][39][40][41][42][43]. In 1990, a linear analytical model that include the Poisson coupling was proposed by Lesmez et al [34] to perform the modal analysis of vibrations in liquid-filled piping system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is worth to explore the dynamics of the straight-curved combination fluid-conveying pipe. Indeed, a few researchers have studied this kind of pipe [34][35][36][37][38][39][40][41][42][43]. In 1990, a linear analytical model that include the Poisson coupling was proposed by Lesmez et al [34] to perform the modal analysis of vibrations in liquid-filled piping system.…”
Section: Introductionmentioning
confidence: 99%
“…Their numerical results indicated that the effect of the static deformation of the pipe on the natural frequencies of the pinned-pinned pipe or the pinned-sliding bearing-pinned pipe was pronounced, while for pinned-pinned pipe, this effect could be ignored. Based on the active learning Kriging model, Zhao et al [41] first investigated the resonance failure of the straight-curved combination pipe conveying fluid and a failure performance function was built. The finite volume method was applied by Guo et al [42] to study fluid-induced vibrations of the Z-shaped pipe with different supports and the effects of the supports on the vibration amplitude of the pipeline.…”
Section: Introductionmentioning
confidence: 99%